Efficacy and safety of new anti-CD20 monoclonal antibodies versus rituximab for induction therapy of CD20(+) B-cell non-Hodgkin lymphomas: a systematic review and meta-analysis - Luo, Chengxin (Sci Rep, 2021)
Rituximab combined with chemotherapy is the first-line induction therapy of CD20 positive B-cell non-Hodgkin lymphomas (CD20(+) B-NHL). Recently new anti-CD20 monoclonal antibodies (mAbs) have been developed, but their efficacy and safety compared with rituximab are still controversial. We searched MEDLINE, Embase, and Cochrane Library for eligible randomized controlled trials (RCTs) that compared new anti-CD20 mAbs with rituximab in induction therapy of B-NHL. The primary outcomes are progression-free survival (PFS) and overall survival (OS), additional outcomes include event-free survival (EFS), disease-free survival (DFS), overall response rate (ORR), complete response rate (CRR) and incidences of adverse events (AEs). Time-to-event data were pooled as hazard ratios (HRs) using the generic inverse-variance method and dichotomous outcomes were pooled as odds ratios (ORs) using the Mantel–Haenszel method with their respective 95% confidence interval (CI). Eleven RCTs comprising 5261 patients with CD20(+) B-NHL were included. Compared with rituximab, obinutuzumab significantly prolonged PFS (HR 0.84, 95% CI 0.73–0.96, P = 0.01), had no improvement on OS, ORR, and CRR, but increased the incidences of serious AEs (OR 1.29, 95% CI 1.13–1.48, P < 0.001). Ofatumumab was inferior to rituximab in consideration of ORR (OR 0.73, 95% CI 0.55–0.96, P = 0.02), and had no significant differences with rituximab in regard to PFS, OS and CRR. (131)I-tositumomab yielded similar PFS, OS, ORR and CRR with rituximab. (90)Y-ibritumomab tiuxetan increased ORR (OR 3.07, 95% CI 1.47–6.43, P = 0.003), but did not improve PFS, DFS, OS and CRR compared with rituximab. In conclusion, compared with rituximab in induction therapy of CD20(+) B-NHL, obinutuzumab significantly improves PFS but with higher incidence of AEs, ofatumumab decreases ORR, (90)Y-ibritumomab tiuxetan increases ORR.